Effect of TCDD exposure in adult female and male mice on the expression of miRNA in the ovaries and testes and associated reproductive functions - Hall, Alina; Mattison, Donald; Singh, Narendra; Chatzistamou, Ioulia; Zhang, Jiajia; Nagarkatti, Mitzi; Nagarkatti, Prakash (Frontiers in Toxicology, 2023)
2,3,7,8-Tetrachlorodibenzo-p-dioxin (TCDD) is an environmental contaminant found widely across the world. While animal and human studies have shown that exposure to TCDD may cause significant alterations in the reproductive tract, the effect of TCDD on the expression of miRNA in the reproductive organs has not been previously tested. In the current study, we exposed adult female or male mice to TCDD or vehicle and bred them to study the impact on reproduction. The data showed that while TCDD treatment of females caused no significant change in litter size, it did alter the survival of the pups. Also, TCDD exposure of either the male or female mice led to an increase in the gestational period. While TCDD did not alter the gross morphology of the ovaries and testes, it induced significant alterations in the miRNA expression. The ovaries showed the differential expression of 426 miRNAs, of which 315 miRNAs were upregulated and 111 miRNA that were downregulated after TCDD exposure when compared to the vehicle controls.In the testes, TCDD caused the differential expression of 433 miRNAs, with 247 miRNAs upregulated and 186 miRNAs downregulated. Pathway analysis showed that several of these dysregulated miRNAs targeted reproductive functions. The current study suggests that the reproductive toxicity of TCDD may result from alterations in the miRNA expression in the reproductive organs. Because miRNAs also represent one of the epigenetic pathways of gene expression, our studies suggest that the transgenerational toxicity of TCDD may also result from dysregulation in the miRNAs.